2013
DOI: 10.1007/s00231-013-1262-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of shock wave propagation in water generated by pulsed arc electrohydraulic discharges

Abstract: International audienceThe objective of this study is to simulate the propagation of the shock wave in water due to an explosion. The study is part of a global research program on the development of an alternative stimulation technique to conventional hydraulic fracturing in tight gas reservoirs aimed at inducing a distributed state of microcracking of rocks instead of localized fracture. We consider the possibility of increasing the permeability of rocks with dynamic blasts. The blast is a shock wave generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The decay trends are consistent with the numerical and experimental results. 18,22 In Fig. 6, it was found that the acoustic pressure from the CNFs-PDMS film is The measured acoustic pressure of the prototyped laser ultrasound transducers was compared with the published results ( Table I).…”
mentioning
confidence: 99%
“…The decay trends are consistent with the numerical and experimental results. 18,22 In Fig. 6, it was found that the acoustic pressure from the CNFs-PDMS film is The measured acoustic pressure of the prototyped laser ultrasound transducers was compared with the published results ( Table I).…”
mentioning
confidence: 99%
“…developed in coal #2 after EHD stimulation and that the fractures penetrate through the coal cube. Furthermore, the breakage of the coal is distributed throughout the cube area and this fracturing pattern may be more useful in gas diffusion from the coal matrix compared to the single or gathered fracture/void generated by traditional hydraulic fracturing (Chen et al, 2013).…”
Section: Characterisation Of Coal After Ehd Stimulationmentioning
confidence: 99%
“…The electrical discharge and the propagation of pressure are simulated with a diphasic model developed at CEA (French Alternative Energies and Atomic Energy Commission) and detailed in Refs. . The electrical discharge is described by an increase of enthalpy of water in a small region between the electrodes.…”
Section: Numerical Simulationmentioning
confidence: 99%